Design of strategies for the process of digitalisation and technological modernisation in social services organisations. - Morilla-Luchena, Aleix; Gómez-Rasco, Teresa; Muñoz Moreno, Rocío; Vázquez-Aguado, Octavio (Cuadernos de Trabajo Social, 2025)
This article explores the use of technology by social service professionals during the Covid-19 pandemic, aiming to extract valuable insights to optimise technological transition processes within social organisations. The research views technology as a psychosocial factor in the work environment, assessing its impact on the health and well-being of professionals. A qualitative methodology was employed, utilizing 22 semi-structured interviews with social work professionals in Spain. Data were analysed using Atlas.ti 23 software, following the Grounded Theory approach. The analysis generated 248 codes and 2,543 citations, of which 57 codes were consolidated under the central theme "Use of technological means". The findings indicate that the use of technological tools during the Covid-19 pandemic helped to reduce the burden of physical documentation, enhance professional coordination-both within organisations and with external entities-and optimise professional-client interactions, among other benefits. The conclusions provide a general framework for designing strategies to facilitate technological transitions in social service organisations, ensuring that technological innovations not only improve workflow efficiency but also enhance the quality of life for professionals within these organisations.